ANALYSIS ON FINANCIAL EFFICIENCY SYNERGY ON PUBLIC COMPANIES IN THE PRIMARY SECTOR AND INDUSTRY POST MONETARY CRISIS LISTED IN JSX - Christnatalia Christnatalia (Business and Entrepreneurial Review, 2010)
The background of this research was merger and acquisition wave frequently in higher research and development needed and new technology implemented companies related in chemical createlower financial performance after merger and acquisition. The objective of this research was to test the significance of the difference between the efficiency financial performance before andafter merger and acquisition. The design of this research applied purposive random sampling, quantitative method two means difference model, and statistic software SPSS for problem solving.Data analysis applied measuring return on capital employed. The result of research indicated that merger and acquisition activities can not improved efficiency of emittens or ROCE ratio in all emittens were getting worse after merger and acquisition